Wnt Signaling Pathway Dysregulation in the Aging Brain: Lessons From theOctodon degus - Inestrosa, Nibaldo C.; Tapia-Rojas, Cheril; Lindsay, Carolina B.; Manuel Zolezzi, Juan (My University, 2020)
Wnt signaling constitutes a fundamental cellular and molecular pathway, necessary from proper embryogenesis to function-maintenance of fully developed complex organisms. In this regard, Wnt pathway plays a crucial role in both the development of the central nervous system and in maintaining the structure and function of the neuronal circuits, and it has been suggested that its dysregulation is critical in the onset of several pathologies including cancer and neurodegenerative disorders, such as Alzheimer's disease (AD). Due to its relevance in the maintenance of the neuronal activity and its involvement in the outbreak of devastating diseases, we explored the age-related changes in the expression of Wnt key components in the cortex and hippocampus of 7 to 72-months-oldOctodon degus(O. degus), a Chilean long-living endemic rodent that has been proposed and used as a natural model for AD. We found a down-regulation in the expression of different Wnt ligands (Wnt3a, Wnt7a, and Wnt5a), as well as in the Wnt co-receptor LRP6. We also observed an increase in the activity of GSK-3 beta related to the down-regulation of Wnt activity, a fact that was confirmed by a decreased expression of Wnt target genes. Relevantly, an important increase was found in secreted endogenous Wnt inhibitors, including the secreted-frizzled-related protein 1 and 2 (SFRP-1 and SFRP-2) and Dickkopf-1 (Dkk-1), all them antagonists at the cell surface. Furthermore, treatment with Andrographolide, a labdane diterpene obtained fromAndrographis paniculata, prevents Wnt signaling loss in agingdegus. Taken together, these results suggest that during the aging process Wnt signaling activity decreases in the brain ofO. degus.
Keywords: wnt signaling; aging; o; degus; neurodegeneration; alzheimers' disease